MODULATION IN GLYCOGEN OF THE FRESHWATER FISH OPHIOCEPHALUS PUNCTATUS EXPOSED TO CYPERMETHRIN - S. GIJARE SHRUTI; I. A. RAJA; V. T. TANTARPALE; K. M. KULKARNI (The Bioscan, 2011)
The effect of cypermethrin on glycogen in liver and intestine of Ophiocephalus punctatus exhibited notable alterations. Liver and intestine being the main site of metabolic activity in body was selected for the study purpose. The sub lethal concentration of cypermethrin treated with Ophiocephalus punctatus at different time interval and in the treated liver and intestine, glycogen content showed declined trend.